(untitled) (Journal of the College of Basic Education, 2026)
The study aimed to reveal the impact of the applications of artificial intelligence in the development of teaching skills in the subject of methods of teaching art education from the point of view of students of the Department of Art Education for the subject of methods of teaching art education in Baghdad. In order to achieve the objectives of the study, the semi-experimental curriculum was adopted through the application of the questionnaire as a study tool to a sample of 60 male and female students of the teaching methods of art education who were distributed in two groups; The control group (taught in the traditional way) consists of 30 students, and the experimental group (taught through the employment of artificial intelligence applications) consists of 30 students.The results of the study showed that the arithmetic average of the use of artificial intelligence applications in the educational process of the tribal measurement control group was 2.95, compared to the experimental group dimensional measurement was 3.80, and the arithmetic average of the total teaching skills of the control group tribal measurement (2.95) while the arithmetic average of the total teaching skills of the experimental group dimensional measurement (3.84).The results also showed differences in the effectiveness of the use of artificial intelligence applications in the educational process when using artificial intelligence applications for the benefit of the experimental group taught through artificial intelligence applications, and the results showed clear differences between the average grades of students of the Department of Technical Education for all teaching skills. (Planning skill, implementation skill, evaluation skill) Teachers of art education teaching methods from the point of view of students of the Department of Art Education between tribal and remote measurement where the differences were in favor of dimensional measurement (experimental group) taught through the employment of the application of artificial intelligence. The study recommended the need to provide workshops and continuous training courses for teachers on the use of artificial intelligence applications, with a focus on developing their skills in dealing with these technologies to make the most of them in the educational process.